Peningkatan Membaca dengan Metode Bercerita di Kelas 1 SD - Wisrayani Wisrayani; Andra Bella Riandini; Wahyullah Alannasir; Riskyanti Ramadhani; Cintia Aulia Ramadhani (CV. Alim's Publishing, 2026)
Reading ability is a fundamental skill that must be mastered by first-grade elementary school students as a foundation for understanding various subjects. However, in practice, many students still experience difficulties in early reading, such as recognizing letters, combining syllables, and understanding simple words. One alternative method that can be used to address this issue is the storytelling method in learning activities. This study aims to describe the effectiveness of the storytelling method in improving the reading ability of first-grade elementary school students. This research employs a qualitative approach using a literature study method. Data were collected from various sources, including scientific journals, books, and relevant previous studies published within the last five years. The data collection technique was carried out through documentation, while data analysis used content analysis by reviewing, comparing, and synthesizing findings from different sources. The results of the study indicate that the storytelling method is effective in improving students’ early reading skills. This method enhances students’ reading interest, enriches their vocabulary, and helps them recognize letters and words more easily in an enjoyable learning environment. In addition, storytelling creates an interactive classroom atmosphere and increases student engagement in the learning process. In conclusion, the storytelling method is an effective and relevant instructional strategy to improve the reading ability of first-grade elementary school students. Therefore, it is recommended as an innovative approach to support the development of early literacy skills.